PERAN HUKUM INTERNASIONAL DALAM MENANGANI KASUS CYBER CRIME - Febrian, Wahyu Rifqi; Faturrahman, Raden Mohammad Rangga; Rahmadina, Hannah Syahida; Deni, Fitra (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
Cybercrime is a crime committed through computer networks as the main tool of the perpetrator in carrying out his actions. This type of cybercrime includes several illegal activities such as hacking, phishing, ransomware, malware, identity theft, and so on. Cybercrime has become a global threat that requires international cooperation to overcome. Cybersecurity is currently a fundamental thing that must be considered by the community or government. A weak cyber security system will become the target of hackers in carrying out their actions. Not only that, the weak law enforcement in handling this case is also a gap for hackers to always do their actions. Therefore, various instruments such as conventions on cyber crime, international law, and international cooperation are the main weapons in dealing with cyber crime. In this article, the author will analyze how the role of international law in dealing with cybercrime cases, including existing mechanisms and instruments as well as the challenges faced and the effectiveness of international cooperation in fighting cybercrime networks. This research aims to find out the role of international law in handling cybercrime cases, challenges in the application of international law, international legal instruments and the effectiveness of international cooperation. This research uses a qualitative approach with document analysis and case studies to explore the effectiveness and weaknesses of international law in dealing with cyber crime. The results found that the role of international law is still not maximized due to various challenges in its implementation, but with Indonesia not ratifying the Budapest Convention, this hampers the role of international legal instruments in tackling cyber crime cases in Indonesia. Despite this, the role of international law is still needed to maximize the opportunities for international cooperation carried out by the authorities in fighting cybercrime cases.